The Synergistic Effect of Muscle, Coordination, and Concentration on the Effectiveness of Jump Floating Serve: A Path Analysis Approach - Fair Muda; Nuridin Widya Pranoto; Muhamad Sazeli Rifki; Ahmad Chaeroni; Dally Rahman (Jurnal Penelitian Pendidikan IPA, 2023)
The research addresses the low proficiency in executing jump floating serves among volleyball players, influenced by factors such as arm muscle explosive power, leg muscle explosive power, hand-eye coordination, and concentration. The study aimed to evaluate the impact of these factors on players' jump floating serve abilities. Using a quantitative approach and survey method, data were collected from 24 male volleyball players at Padang State University. The instruments included the jump floating serve test, One Hand Medicine Ball Put for arm muscle explosive power, Vertical Jump Test for leg muscle explosive power, ball throw response for hand-eye coordination, and Grid Concentration Test for concentration. Path analysis was utilized for data analysis. The results revealed: (1) a significant direct impact of arm muscle explosive power on jump floating serve ability (Py1= 0.358), (2) no significant direct impact of leg muscle explosive power on jump floating serve ability (Py2= 0.119), (3) a significant direct impact of hand-eye coordination on jump floating serve ability (Py3= 0.343), and (4) a significant direct impact of concentration on jump floating serve ability (Py4= 0.251). Additionally, there were no direct effects of arm muscle explosive power, leg muscle explosive power, or hand-eye coordination on concentration (P41= 0.043, P42= 0.242, P43= 0.427). However, indirect effects on jump floating serve ability through concentration were found for arm muscle explosive power (ꜫ1 = 0.090), leg muscle explosive power (ꜫ2 = 0.029), and hand-eye coordination (ꜫ3 = 0.107).